Pediatric Peritoneal Epithelial Malignant Mesothelioma Case Report - Elizabeth Bellew; Samantha Lee; null Hiren Patel; Carolyn Fein Levy; Rachelle Goldfisher; John Amodio (Case Reports in Radiology)
We present a 14-year-old boy with peritoneal epithelial malignant mesothelioma (PEMM). While pathology is required to make this diagnosis, radiology plays a crucial role throughout the clinical course of this disease. The key imaging characteristics of peritoneal mesothelioma have been previously well-described in the adult population, but there are rare reports in the pediatric population. This pediatric report highlights the multidimensional use of imaging in this disease, from the initial evaluation to therapeutic supplementation and subsequent follow-up.